Global child : children and families affected by war, displacement and migration - Denov, Myriam S. 1970- HerausgeberIn; Mitchell, Claudia 1948- HerausgeberIn; Rabiau, Marjorie HerausgeberIn (Genocide, political violence, human rights series, 2023)
"Armed conflicts continue to wreak havoc on children and families around the world with profound effects. In 2017, 420 million children-nearly one in five-were living in conflict-affected areas, an increase in 30 million from the previous year. The recent surge in war-induced migration, referred to as a "global refugee crisis" has made migration a highly politicized issue, with refugee populations and host countries facing unique challenges. We know from research related to asylum seeking families that it is vital to think about children and families in relation to what it means to stay together, what it means for parents to be separated from their children, and the kinds of everyday tensions that emerge in living in dangerous, insecure, and precarious circumstances. In this book, we draw on what we have learned through our collaborative undertakings, and highlight the unique features of participatory, arts-based, and socio-ecological approaches to studying war-affected children and families, demonstrating their collective strength, as well as their limitations and ethical implications. Building on work across the Global South and the Global North, this book aims to deepen an understanding of our tri-pillared approach, and the potential for contributing to improved practices in working with war-affected children and their families"--